Financial inclusion gaps among women entrepreneurs: a rural-urban analysis in Mexico, 2021 - Pérez Morales, Lucía Guadalupe; Vega Macías, Daniel; López Mateo, Celina (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To compare the levels of financial inclusion of women entrepreneurs based on the size of their locality of residence (rural, low-urban, medium-urban, and upper-urban areas,) in the Northeast and Western–Bajío regions of Mexico. MATERIAL AND METHOD: A quantitative analysis was conducted. The sample consisted of 372 women entrepreneurs, distributed across four locality strata: rural (n=65), lower-urban (n=42), middle-urban (n=64), and upper-urban (n=201). Three dimensions of financial inclusion (access, use, and quality) were evaluated using the Chi-square test (p<0.05) to identify statistically significant differences among strata. RESULTS: Women in rural areas present a clear disadvantage in access to and use of formal financial products—such as payroll accounts (1.5% vs. 19.4% in high-urban areas), bank loans (4.6% vs. 18.4%), and Afore retirement accounts (6.3% vs. 39.4%)—demonstrating a greater reliance on informal mechanisms. CONCLUSIONS: The study highlights the need to design differentiated, gender-sensitive financial inclusion policies that prioritize women entrepreneurs in rural areas. These interventions, aimed at overcoming the identified barriers to access and use, represent a crucial strategy for reducing socioeconomic vulnerability and improving the quality of life of this segment of the population.